Chronostratigraphy and geomorphology of washover fans in the Exmouth Gulf (NW Australia) – A record of tropical cyclone activity during the late Holocene. (1st August 2017) - May, Simon Matthias; Brill, Dominik; Leopold, Matthias; Callow, John Nikolaus; Engel, Max; Scheffers, Anja; Opitz, Stephan; Norpoth, Maike; Brückner, Helmut
Abstract: Washover fans typically form due to barrier overwash or breaching and coastal inundation and generally represent geomorphological and depositional evidence of intense storms. Few studies have investigated the chronostratigraphy of washover fans in order to infer magnitude/frequency patterns of extreme-wave events over longer time scales. Here we present new data on the chronostratigraphy of late Holocene washover fans in the Exmouth Gulf (Western Australia) by using ground penetrating radar and unmanned aerial vehicle (UAV) survey techniques, as well as geomorphological, sedimentological and chronological investigations. This study aims to (i) provide a detailed characterization of the washover fans' geomorphology and stratigraphical architecture; (ii) document depositional processes involved in their formation; (iii) establish a chronostratigraphy based on optically stimulated luminescence (OSL); and (iv) understand the significance of the washover fans for recording past tropical cyclone (TC) activity. The fans consist of multiple sequences of sand, shell debris and coral rubble comprising depositional units related to TC-induced inundation. The units are separated by palaeosurfaces with incipient soil formation, formed during periods of reduced depositional activity. In combination with the interpretation of a UAV-based high-resolution digital surface model, multiple phases of reactivation are inferred. OSL results allow the establishment of a local long-term TC record and suggest storm-induced deposition at ∼170, ∼360, ∼850 and ∼1300 years ago. Further units were dated to ∼1950, ∼2300, and ∼2850 years ago. The chronology of TC events is consistent with other work relating TC activity with El Niño Southern Oscillation (ENSO) and sea surface temperature (SST) patterns, corroborating the regional palaeotempestological relevance of this unique geomorphological record. Highlights: This study presents the chronostratigraphy of washover fans in the Exmouth Gulf (WA). The washover fans record tropical cyclones during the last 3000 years. Palaeosol-sediment sequences and OSL results point to episodic fan reactivation. Increased tropical cyclone activity occurred ∼170, ∼360, ∼850 and ∼1300 years ago. The record agrees with other work on tropical cyclone, ENSO and SST patterns.